2008
DOI: 10.1529/biophysj.108.130021
|View full text |Cite|
|
Sign up to set email alerts
|

sNASP, a Histone H1-Specific Eukaryotic Chaperone Dimer that Facilitates Chromatin Assembly

Abstract: NASP has been described as a histone H1 chaperone in mammals. However, the molecular mechanisms involved have not yet been characterized. Here, we show that this protein is not only present in mammals but is widely distributed throughout eukaryotes both in its somatic and testicular forms. The secondary structure of the human somatic version consists mainly of clusters of alpha-helices and exists as a homodimer in solution. The protein binds nonspecifically to core histone H2A-H2B dimers and H3-H4 tetramers bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 85 publications
(101 reference statements)
4
68
0
Order By: Relevance
“…The low caspase-3 activity detected in Jurkat-Tat101 would contribute to MCM3 stability and therefore to the maintenance of the MCM complex, avoiding apoptosis. Other factors related to cell cycle progression, cytokinesis, and cell proliferation were also overexpressed in Jurkat-Tat101, such as NUDC, NASP, and PCNA (102)(103)(104)(105). The overexpression of somatic NASP has been related to changes in NF-B activity (106), which is known to be enhanced by Tat (23,70).…”
Section: Discussionmentioning
confidence: 99%
“…The low caspase-3 activity detected in Jurkat-Tat101 would contribute to MCM3 stability and therefore to the maintenance of the MCM complex, avoiding apoptosis. Other factors related to cell cycle progression, cytokinesis, and cell proliferation were also overexpressed in Jurkat-Tat101, such as NUDC, NASP, and PCNA (102)(103)(104)(105). The overexpression of somatic NASP has been related to changes in NF-B activity (106), which is known to be enhanced by Tat (23,70).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoplasmin, when heavily phosphorylated and otherwise modified in the egg, decondenses sperm chromatin (Philpott et al , 1991) yet binds and sequesters core histones (Onikubo et al , 2015). NASP participates in H3-H4 dimer assembly in the cytoplasm (Campos et al , 2010), stores H3-H4 in the egg (Finn et al , 2012), and also directly transfers linker histones into the nucleus (Finn et al , 2008). Asf1 is a histone chaperone responsible for H3-H4 import into nucleus, but Asf1 has also been implicated in the disassembly of nucleosomes during DNA replication and during transcription (English et al , 2006).…”
Section: Histones and Histone Chaperones: Key Function And Insight Frmentioning
confidence: 99%
“…Newly synthesized histone H3 -H4 dimers are delivered to the replication fork by ASF1 for deposition by CAF-1 (4) or, in the case of histone H2A-H2B dimers, by NAP1 (5). and histone dynamics; for example, nuclear autoantigenic sperm protein (NASP), initially reported as a histone H1 linker chaperone (Finn et al 2008), was later found to function as an H3 -H4 chaperone (Osakabe et al 2010) as part of a multichaperone complex Groth et al 2005). Recent work indicates that NASP may act to fine-tune soluble H3 levels by counteracting degradation involving the chaperone-mediated autophagy pathway (Cook et al 2011).…”
Section: Dm Macalpine and G Almouznimentioning
confidence: 99%